ESTETIKA KALIGRAFI ISLAM DAN IMPLIKASINYA DENGAN ILMU TASAWUF - Cincin Hasani; Euis Fitri Yani; Muhammad Drajat Bima Putra (Yayasan Haiah Nusratul Islam, 2025)
Sufi thought had a profound impact on the development of the aesthetics of Islamic calligraphy, making it more than just a visual art, but also a manifestation of Islamic spirituality. The teachings of Sufism, which emphasize divine love, tawhid (oneness of God), and the concept of fana (elimination of ego), are reflected in beautiful calligraphic works that are full of symbolic meaning. Each stroke of a letter in calligraphy is not only a decorative element, but also a means of contemplation and union with the Creator. Elements such as harmony of lines, compositional balance, and white space in calligraphy reflect the principles of Sufism, including simplicity and oneness with God. Furthermore, the symbolism of Arabic letters is often associated with Sufi teachings, giving this art a deep spiritual dimension. This article aims to explore how Sufi thought influences the visual elements and spiritual meanings in Islamic calligraphy, thereby strengthening the connection between art, spirituality and aesthetics in the Islamic tradition.